Development Of An Android Based Application For A Certification Management Information System For A Certification Institute: Design And Implementation - Sembiring, David Jumpa Malem; Br Perangin-angin, Sinek Mehuli; Br Surbakti, Asprina; Br Ginting, Devita Permata Sari (SEAN Institute, 2024)
Society will undergo significant changes with the development of information technology. The role of management information systems at this time is very much needed by seeing the rapid advancement of technology. Of course, this needs to make people improve and keep up with the developments in the era of Industry 4.0, so as not to be left behind by technological developments, so that they can benefit from it by managing data through a mobile application-based management information system. Writing this article uses the literature review method, which includes the stages of identifying the problem, searching for relevant studies to clarify, and drawing conclusions to answer the problem. On the basis of the results of the literature review, the conclusion is that management information systems have positive effects on society by providing effective and efficient information. In order to be able to support activities, the application of information systems can be adapted and designed according to their respective needs. It can be said that facing the digital era, the application of information systems is much better.